Outside clinical setting experience in a public hospital and oral health promotion - Medeiros Júnior, Antonio; Alves, Maria do Socorro Costa Feitosa; Nunes, Jussara de Paiva; Costa, Iris do Céu Clara (Revista de Saúde Pública, 2005)
OBJECTIVE: To describe a teaching aid activity aimed at providing experience for promoting collective oral health to graduating dental students. METHODS: This experience was based on the evaluation of students' performance as oral health educators as they had, among other duties, to motivate inpatients and their families to practice healthy habits aiming at a comprehensive and more human care of hospitalized patients. RESULTS: The results show that oral hygiene was incorporated into hospital routine, evidenced by the differences between baseline and final dental biofilm indices (1.72 and 1.17, respectively). Using the U-Mann-Whitney test, this difference was extremely significant (p